CURRICULUM PER EXPERIENCE FIELDS IN EARLY CHILDHOOD EDUCATION: IS IT (STILL) POSSIBLE TO PROMOTE OBUTCHENIE? - Pasqualini, Juliana Campregher [UNESP]; Martins, Ligia Marcia [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
This paper presents a general characterization and critical examination of what the current Brazilian legislation for Early Childhood Education imposes, with the aim of exploring possible paths for the formulation of curricular proposals of historical-critical orientation in the face of the notion of experience fields. Based on the analysis of the chapter of the Base Nacional Comum Curricular (National Common Curricular Base) dedicated to Early Childhood Education and the document Campos de experiencias: efetivando direitos e aprendizagens na Educacao Infantil (Experience fields: assuring rights and learning in Early Childhood Education), launched in 2018, valid aspects are identified at the same time as the persistence of the anti-schooling approach and its liberal and idealistic conception of education is problematized. The paper concludes with the search for possible paths for pedagogical work, by focusing children's experiences and their contents.
Keywords: Early childhood education; National Common Curricular Base; Critical-historical pedagogy; Vygotski